The expression of humour in print advertising - Jurgaitytė, Irma (Lietuvių kalba, 2017)
By means of any communication of advertising, it is striven to draw an addressee’s attention, to interest him/her, and, finally, to determine the self-determination to purchase the item or to use the advertised service. In order to achieve the aim, humour is often used. This is an ability to notice funny phenomena of reality, gaiety, tolerant, without hurting derision: being a specific means of communication, it creates a pleasant and positive microclimate of communication. In the advertisements of emotional nature it is not attempted to present constructive and logically grounded information, but it is appealed to a person’s emotions. The language of emotions is close to spoken language, so spoken language actualized in the texts of advertising creates the illusion of direct contact and personality, enhances the interest and promotes an addressee to react. The article analyses linguistic humour expression of print advertising. The descriptive and semantic analysis methods employed in the research helped to analyse and discuss the characteristic means of spoken language which are used to create quips, language plays. It was determined that in print advertising the situation of dialogue is actualized. It is supported with words denoting emotions inherent to spoken language – such words are unexpected and so often witty. The expression of humour is different, but often the usual lexical means are employed: diminutives, neologisms, and jargons. Humour is usually created on the basis of word play, personification and irony, it is often strengthened with silent language – non-verbal language elements covering postures, grimaces, and colours.